Association Between Air Pollutants and Pediatric Respiratory Outpatient Visits in Zhoushan, China - Liu, Wen-Yi; Yi, Jing-Ping; Shi, Leiyu; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Objective: This study aimed to explore the time-series relationship between air pollutants and the number of children's respiratory outpatient visits in coastal cities. Methods: We used time series analysis to investigate the association between air pollution levels and pediatric respiratory outpatient visits in Zhoushan city, China. The population was selected from children aged 0-18 who had been in pediatric respiratory clinics for eight consecutive years from 2014 to 2020. After describing the population and weather characteristics, a lag model was used to explore the relationship between outpatient visits and air pollution. Results: We recorded annual outpatient visits for different respiratory diseases in children. The best synergy lag model found a 10 μg/m3 increase in PM2.5 for every 4%–10% increase in the number of pediatric respiratory outpatient visits. (P <0.05). The cumulative effect of an increase in the number of daily pediatric respiratory clinics with a lag of 1–7 days was the best model. Conclusions: PM2.5 is significantly related to the number of respiratory outpatient visits of children, which can aid in formulating policies for health resource allocation and health risk assessment strategies.